A review of available methods and development on energy storage; Technology update - Mahlia T.M.I.; Saktisahdan T.J.; Jannifar A.; Hasan M.H.; Matseelar H.S.C. (Elsevier Ltd, 2023)
Energy storage becomes a key element in achieving goals in energy sustainability that lead to energy and cost savings. This paper discusses various types of energy storage including compressed air energy storage (CAES), flywheel energy storage (FES), pumped hydro energy storage (PHES), battery energy storage (BES), flow battery energy storage (FBES), superconducting magnetic energy storage (SMES), super capacitor energy storage (SCES), hydrogen energy storage, synthetic fuels, and thermal energy storage (TES) with additional information about the recent update of the technology. In the final part of this paper, the comparison and barriers to deploying the technologies are also given in order to give a better view about the energy storage technique. © 2014 Elsevier Ltd.